Nonadherence behaviors and some related factors in kidney transplant recipients - Pari Hedayati; Nahid Shahgholian; Ahmad Ghadami (Wolters Kluwer Medknow Publications, 2017)
Background: Kidney transplantation is the renal replacement therapy of choice for most patients with end-stage renal disease (ESRD), however, adherence to the recommended lifestyle is critical for a positive prognosis. The purpose of this study was to assess adherence to immunosuppressive therapy and lifestyle recommendations along with some related factors among kidney transplant patients. Materials and Methods: In this descriptive analytical study, all patients completed a questionnaire regarding medication intake and lifestyle recommendations (preventing of infection, self-monitoring, prevention of cardiovascular disease (CVD), and sun protection). The participants were divided into 4 groups according to the level of adherence (good, partial, poor, and nonadherent) indicated in their responses. Results: Most kidney recipients were adherent to their drug prescriptions, but were partial, poor, or nonadherent regarding lifestyle recommendations. Increased passage of time since transplantation and low family support and educational level resulted in nonadherence. Men showed greater adherence to medication intake than women. Patients with lower number of drugs and reported drug side-effects illustrated better adherence to medication intake. Women adhered to infection protection recommendations more than men, and older and married patients adhered to cardiovascular prevention recommendations more than others. However, younger patients showed greater adherence to self-monitoring recommendations, and singles, young individuals, and women were adherent to sun protection recommendations. Conclusions: Nonadherence is common among kidney transplant recipients. Thus, it is necessary to determine patients who are at risk of nonadherence and to introduce more educational programs to improve their adherence and their quality of life (QOL).